2009
DOI: 10.1002/jcb.22406
|View full text |Cite
|
Sign up to set email alerts
|

Non‐resorbing osteoclasts induce migration and osteogenic differentiation of mesenchymal stem cells

Abstract: Osteoclast activity has traditionally been regarded as restricted to bone resorption but there is some evidence that also non-resorbing osteoclasts might influence osteoblast activity. The aim of the present study was to further investigate the hypothesis of an anabolic function of non-resorbing osteoclasts by investigating their capability to recruit mesenchymal stem cells (MSC) and to provoke their differentiation toward the osteogenic lineage. Bone-marrow-derived human MSC were exposed to conditioned media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 45 publications
6
43
0
Order By: Relevance
“…A distinct feedback of the osteoclasts on osteoblasts is shown for the gene expression of BSP II, which is clearly most intensive for modifications III and IV -the only modifications which facilitated the formation of large C Heinemann et al Osteoblast/osteoclast co-culture for biomaterials testing multinuclear osteoclasts. Similar results have been recently published by Kreja et al whereby BSP II mRNA expression was up-regulated after stimulation of hBMSC with conditioned media collected from human osteoclasts (Kreja et al, 2010). Taking into account both the differentiation of hBMSC and hMc, modification III seems to be best-suited for cocultivation of human osteoblasts and osteoclasts in the present case.…”
Section: Heinemann Et Al Osteoblast/osteoclast Co-culture For Biomsupporting
confidence: 91%
“…A distinct feedback of the osteoclasts on osteoblasts is shown for the gene expression of BSP II, which is clearly most intensive for modifications III and IV -the only modifications which facilitated the formation of large C Heinemann et al Osteoblast/osteoclast co-culture for biomaterials testing multinuclear osteoclasts. Similar results have been recently published by Kreja et al whereby BSP II mRNA expression was up-regulated after stimulation of hBMSC with conditioned media collected from human osteoclasts (Kreja et al, 2010). Taking into account both the differentiation of hBMSC and hMc, modification III seems to be best-suited for cocultivation of human osteoblasts and osteoclasts in the present case.…”
Section: Heinemann Et Al Osteoblast/osteoclast Co-culture For Biomsupporting
confidence: 91%
“…Concerning the interspecies potency of the osteogenic factors demonstrated here, Pederson et al (2008) first reported that RAW264.7 osteoclast-like cells secrete soluble sphingosine 1 phosphate (S1P) and BMP6 which can differentiate hMSC into mineralising osteoblasts. Various other osteoclast-expressed osteogenic factors such as PDGF-BB (Kreja et al, 2010), Wnt10b (Pederson et al, 2008), other BMPs (McCullough et al, 2007, and the recently identified coupling factor CTHRC1 (Takeshita et al, 2013) may have also played a role.…”
Section: Nl Davison Et Al Surface Architecture Of Tricalcium Phosphatementioning
confidence: 99%
“…Additionally, surface architecture may also impact other biological processes important for bone formation such as vasculogenesis and stem cell recruitment. Interestingly, many of the same osteogenic factors that are expressed by osteoclasts and their monocyte/macrophage precursors have also been shown to chemotactically home pre-osteoblasts (OSM, PDGF, CTHRC1) and stimulate blood vessel formation (TNF-α) (Kreja et al, 2010;Glass et al, 2011;Takeshita et al, 2013). For instance, invading macrophages signalled by the foreign body response may preferentially secrete cytokines important for both blood vessel formation and stem cell recruitment (e.g., pericytes) (Bergers and Song, 2005), followed by osteoblast/osteoclast differentiation (Fellah et al, 2010) -all in response to surface architecture.…”
Section: Nl Davison Et Al Surface Architecture Of Tricalcium Phosphatementioning
confidence: 99%
See 1 more Smart Citation
“…PDGF-BB is believed to mobilize cells of mesenchymal origin, stabilize newly formed vessels and orchestrate cellular components for osteoblast differentiation 33 . It has been reported that osteoclasts secret PDGF-BB to induce migration of MSCs or osteoblasts 3436 .…”
Section: Introductionmentioning
confidence: 99%